Police worker politics in India, Brasil, and beyond - Jauregui, Beatrice (Policing and society, 2022)
This article conceives a new conceptual framework of ‘police worker politics’ (PWP) as a means to inspire critical research on how the political significance and legitimacy of police configure concepts and practices of democratic governance. Drawing on anthropological theories and methodologies of disjunctive comparison, I consider public policing as work, and figure public police officials as political actors who mobilise around their identities as workers in ways that may be more or less legitimate in the eyes of the governments and the publics they serve. I focus on two major forms of PWP—police unionism and police strikes—and analyze how they have manifested historically in two of the world’s most populous and pluralistic democratic states: India and Brazil. Comparing institutional structures and specific events of PWP in these two Global South postcolonies, I aim 1) to better understand how police worker politics and their legitimacy are co-configured with processes of decolonisation and democratisation; 2) to energise more theoretically nuanced and empirically grounded debates on police worker politics as an understudied global form ripe for comparative research, and 3) to generate and contribute to collaborative inquiries in the emerging field of comparative policing studies generally.